(untitled) (Swiss Medical Weekly, 2012)
Depending on the populations studied and the definitions applied, the prevalence of treatment-resistant hypertension varies from 10% to 15%, but is higher in conditions associated with increased sympathetic drive, such as obesity, obstructive sleep apnoea, diabetes or renal dysfunction. The Symplicity studies recently demonstrated that reducing sympathetic tone by intravascular renal denervation is feasible in treatment-resistant hypertension, but failed to provide conclusive evidence on the size and durability of the antihypertensive, renal and sympatholytic effects, long-term safety, quality of life, the possibility to relax antihypertensive drug treatment, cost-effectiveness, and long-term hard cardiovascular-renal outcomes. Renal denervation should therefore only be offered within a clinical research context at highly skilled tertiary referral centres that participate in international registries constructed independent of the manufacturers.